PENGARUH KEADILAN PROSEDURAL DAN KOMITMEN ORGANISASIONAL TERHADAP PERILAKU SUKA RELA (ORGANIZATIONAL CITIZENSHIP BEHAVIOR) PEGAWAI PADA BADAN PENDAPATAN DAERAH PROVINSI KALIMANTAN TIMUR - Lisna Adriani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This study aims to determine and analyze the effect of procedural justice and organizational commitment on voluntary behavior or Organizational Citizenship Behavior (OCB) of employees at the Regional Revenue Agency of East Kalimantan Province. This research is quantitative research, and measured according to its level of exploitation is an associative study. Data obtained through questionnaires, observation, and documentation were analyzed by testing the hypothesis using product-moment correlation, simple linear regression analysis, and continued with the coefficient of determination or coefficient of determination. The results showed that procedural justice has a positive and significant relationship with the Organizational Citizenship Behavior (OCB), organizational commitment has a positive and significant relationship with the Organizational Citizenship Behavior (OCB) of Employees at the Regional Revenue Agency of East Kalimantan Province.Keywords: Procedural Justice, Organizational Commitment, Organizational Citizenship Behavior